2021
DOI: 10.1590/2326-4594-jiems-2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Membrane Glycoprofiling in a PMM2-CDG Patient

Abstract: Congenital disorders of glycosylation (CDG) are metabolic hereditary diseases caused by defects in the synthesis of glycoconjugates. CDG have been described in sugar-nucleotide biosynthesis and transporter, glycosyltransferases, vesicular transport, as well as in lipid biosynthesis and glycosylphosphatidylinositol anchors. PMM2-CDG is caused by mutations in the phosphomannomutase-2 (PMM2) gene and shows autosomal recessive inheritance. It affects all organs and tissues, ranging from severe psychomotor retardat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Based on disease pathology, one might expect a decrease in lectin binding in PMM2-CDG patient cells, due to hypoglycosylation. In fact, hypoglycosylation of serum transferrin is used to diagnose patients with CDG and reduced lectin binding has been observed in PMM2-CDG patient derived platelets, induced pluripotent stem cells and EBV transformed B cells (22,(40)(41)(42). Eventhough it was not addressed in this study, the increased lectin binding in PMM2-CDG patient monocytes that we observed could be explained by subtle differences in activation status that alter glycoprotein expression and therefore glycocalyx composition.…”
Section: Discussionmentioning
confidence: 68%
“…Based on disease pathology, one might expect a decrease in lectin binding in PMM2-CDG patient cells, due to hypoglycosylation. In fact, hypoglycosylation of serum transferrin is used to diagnose patients with CDG and reduced lectin binding has been observed in PMM2-CDG patient derived platelets, induced pluripotent stem cells and EBV transformed B cells (22,(40)(41)(42). Eventhough it was not addressed in this study, the increased lectin binding in PMM2-CDG patient monocytes that we observed could be explained by subtle differences in activation status that alter glycoprotein expression and therefore glycocalyx composition.…”
Section: Discussionmentioning
confidence: 68%
“…These disorders (CDG) are genetic diseases caused by deficient glycoprotein and glycolipid glycan synthesis and attachment [81][82]. Most are multisystem disorders with variable phenotype severity and neurological involvement.…”
Section: Dystroglycanopathies and Congenital Disorders Of Glycosylationmentioning
confidence: 99%
“…Elucidation of the molecular pathological mechanisms of CDG associated with DG glycosylation abnormalities will be an important issue in understanding the mechanisms of dystroglycanopathies. Characterizing a glycoproteome profile of patients prior to and on treatment will help to better understand the changes of a plethora of glycoproteins and related clinical observations in dystroglycanopathies [81][82]86,97].…”
Section: Dystroglycanopathies and Congenital Disorders Of Glycosylationmentioning
confidence: 99%